One Secret Summer - Lokko, Lesley (London Orion, 2011)
In the perfect family, there's a thin line between love and hate, especially when there's so much to hide. The Keelers are one of those families that seem to have everything. Glamorous, wealthy and privileged, life has always been easy for them, on the outside at least. But even the happiest of families have their secrets.
Keywords: Middle class families -- Family secrets -- Women lawyers